EVALUASI WEB KEGIATAN ORGANISASI MAHASISWA DENGAN MENGGUNAKAN METODE PENGUJIAN END USER COMPUTING SATISFACTION (EUCS): Evaluating Student Activity Web Using EUCS Method - Fatkhur Rohman, Arif; Fitriana, Anis; Maulana, Ryan; Nur Alifah, Putri; Tri Hidayat, Ahmad; Ridwan, Ridwan (Jurnal Komputer dan Teknologi, 2024)
In the continuously evolving digital era, the role of a website in the realm of student organizations has become increasingly crucial in facilitating communication, coordination, and documentation of various activities. The Student Organization Activities website has emerged as a vital tool that enables members to access a range of services, from information provision and proposal submissions to financial reporting. Given the growing complexity and diversity of organizational activities, the Ease of Use (EUCS) of the website becomes a determining factor for success in creating a positive user experience. This research aims to conduct an in-depth evaluation of the EUCS of the Student Organization Activities website by applying EUCS testing methods. The evaluation results indicate that the majority of users are satisfied with the website, particularly in terms of user-friendliness, accuracy of information, and clear presentation. The implications of this research underscore the importance of maintaining interface design consistency, simplicity, and the website's ability to adapt to user preferences to enhance their experience. With these findings, the Student Organization Activities website can continue to be improved to meet the needs and expectations of organization members, contributing to the overall enhancement of the quality of information services provided by student organizations. EUCS evaluation becomes a crucial element in measuring the effectiveness and efficiency of the Student Organization Activities website, aiding in identifying potential usability barriers and facilitating appropriate improvements.